2011
DOI: 10.1186/1472-6882-11-101
|View full text |Cite
|
Sign up to set email alerts
|

Developments on drug discovery and on new therapeutics: highly diluted tinctures act as biological response modifiers

Abstract: BackgroundIn the search for new therapies novel drugs and medications are being discovered, developed and tested in laboratories. Highly diluted substances are intended to enhance immune system responses resulting in reduced frequency of various diseases, and often present no risk of serious side-effects due to its low toxicity. Over the past years our research group has been investigating the action of highly diluted substances and tinctures on cells from the immune system.MethodsWe have developed and tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…To address this problem, our research group has been systematically evaluating medicines that have already been shown to produce target effects against in vitro cancer models. 12 Considering the importance of drug discovery or the implications that could be derived from novel properties of new compounds, we tested M1, a commercial homeopathic medicine used as complementary therapy for cancer, in an experimental mouse model for the skin cancer melanoma. Here, we observed several indications demonstrative of a successfully formulation in the treatment of melanoma: 1) mice treated with M1 have reduced both melanoma metastases and primary tumor formation; 2) tumors of M1 treated mice have reduced angiogenesis and proliferation, while higher levels of tumor death and beta-catenin, which are 'good' prognostic markers; and 3) fewer frequency of the tumor associated MDSC characterized by the markers CD11/Gr-1 in addition to lower expression of AT1R in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this problem, our research group has been systematically evaluating medicines that have already been shown to produce target effects against in vitro cancer models. 12 Considering the importance of drug discovery or the implications that could be derived from novel properties of new compounds, we tested M1, a commercial homeopathic medicine used as complementary therapy for cancer, in an experimental mouse model for the skin cancer melanoma. Here, we observed several indications demonstrative of a successfully formulation in the treatment of melanoma: 1) mice treated with M1 have reduced both melanoma metastases and primary tumor formation; 2) tumors of M1 treated mice have reduced angiogenesis and proliferation, while higher levels of tumor death and beta-catenin, which are 'good' prognostic markers; and 3) fewer frequency of the tumor associated MDSC characterized by the markers CD11/Gr-1 in addition to lower expression of AT1R in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…16 M1 is composed by the following sub-stances diluted in water, with vigorous shaking in-between dilutions, all together in the same flask: Aconitum napellus-20 Hahnemann's dilution (DH), Arsenicum album-18 DH, Asa foetida-20 DH, Calcarea carbonica-16 DH, Chelidonium majus-20 DH, Cinnamon-20 DH, Conium maculatum-17 DH, Echinacea purpurea-20 DH, Gelsemium sempervirens-20 DH, Ipecacuanha-13 DH, Phosphorus 20 DH, Rhus toxicodendron-17 DH, Silicea-20 DH, Sulfur-24 DH, and Thuja occidentalis-19DH, as previously described. 12 Mice and cell line C57BL/6 mice, 7e10 weeks of age (n = 69), were used in experiments according to the approval of the local ethics committee, which certified the procedures using mice in this study are in agreement with the Experimental Animal Brazilian Council and Canadian Council on Animal Care (CEUA certification no 653). Experiments were conducted using pool of mice of equal sex.…”
Section: Derivation Of M1mentioning
confidence: 99%
See 1 more Smart Citation
“…7 de Oliveira et al investigated that the action of highly diluted substances and tinctures on cells from the immune system including Rhus tox, and showed that highly diluted tinctures modulate the immune response. 28 Although, many studies have reported the antiinflammatory and anti-arthritis effect of Rhus tox, the mechanisms underlying the effects observed in both in vivo and in vitro systems remains unclear. This study demonstrates the anti-arthritis activity of homeopathic dilution of Rhus tox using a mouse preosteoblastic cell line model.…”
Section: Discussionmentioning
confidence: 99%
“…Tinctures are alcoholic or partially alcoholic solutions of nonvolatile extracts of vegetable or animal origin drugs or of pure chemical compounds [68]. Tinctures vary in strength but usually do not exceed 10% active principle in strength.…”
Section: Alcoholic Preparationmentioning
confidence: 99%